UNRULY WOMEN IN THE PUBLIC SPHERE: LA BARBE ON LE PETIT JOURNAL - Forrest, Amy E (Sociologias Plurais, 2014)
This article considers the social consequences of transgressing expected norms of gendered behaviour in the public sphere of a mainstream French television programme. La Barbe, who appeared on Le Petit Journal in December 2011, elicited an onslaught of indignant and sardonic public responses via social media. Drawing on Meehan (1995), Fraser (1990, 1995), and Landes (1995), this article analyses the televised appearance and the online reactions. Due to La Barbe’s unsuccessful communication and interested discourse, the public denounced, and so attempted to regulate, feminist disobedience.